ANALYSIS OF PHENOLS AND OXIDATION INTERMEDIATES IN COKING WASTEWATER BY HPLC - Yang, Quo; Liu, Xingyong; Yang, Hu; Ma, Xie; Feng, Yujun (Journal of the Chilean Chemical Society, 2018)
The simultaneous determination of phenol, cresol, polyphenol and their degradation products was important to evaluate the biodegradability of real wastewater. In the present study a reversed phase high performance liquid chromatography method was developed and validated for simultaneous determination of phenol (PhOH), o-cresol (o-C), p-cresol (p-C), hydroquinone (HQ), benzoquinone (BQ), catechol (CTL), p-hydroxybenzoic acid (p-HBZO) and p-hydroxybenzaldehyde (p-BZAL). The developed method was successfully applied to quantitative analysis of these compounds in raw and treated wastewater by CWAO. The highly toxic compounds, HQ and BQ, were totally removed; whereas 52.5% of PhOH, 59.4% of o-C and 57.7% of p-C in coking wastewater were degraded by CWAO over activated carbon catalyst. The degradation products including low-toxicity p-BZAL and p-HBZO were detected in the treated wastewater. The pH of wastewater was important to avoid generation of highly toxic compounds. CWAO using activated carbon as catalyst was feasible for pretreatment of coking wastewater. The established HPLC method was also used to simultaneously analyze phenols in other wastewater.